Program Qur’an Camp Dalam Pencapaian Target Hapalan Siswa - Hadi Habibillah, Muhammad; Pasaribu, Syahrin (Edukais : Jurnal Pemikiran Keislaman, 2023)
Students have difficulty memorizing the Al-Quran because the memorization environment is not conducive, while there is a memorization target that must be achieved every semester. Therefore, in order to increase students' memorization achievements, a Qur'an Camp program was planned to improve students' memorization at SMP Muhammadiyah 47 Medan Sunggal. The aim of this research is to: determine the implementation of the Qur'an Camp carried out by SMP Muhammadiyah 47 Medan Sunggal, and the impact and effectiveness of the implementation of the Qur'an Camp carried out by SMP Muhammadiyah 47 Medan Sunggal. This research is field research with descriptive qualitative methods, namely describing and providing an understanding of phenomena that occur at the research location based on the information obtained. The research results show that the Qur'an camp activity is a student quarantine activity carried out by SMP Muhammadiyah 47 Sunggal. Quarantine is carried out outside the school environment, namely in the Education Field, Jl. Teak. The Qur'an camp program at SMP Muhammadiyah 47 Medan Sunggal was the first on 3-5 November 2023 and was attended by 15 teachers and 20 students. The Qur'an Camp program is an activity to accelerate tahfidz Qur'an by quarantining participants to focus on memorization targets with the aim of accelerating achievement and completing their memorization. Qur'an camp activities have a positive influence on increasing students' targets for memorizing the Qur'an.